Children's Literature in the reading program engaging young readers in the 21st Century - Wooten, Deborah A.; Liang, Lauren A.; Cullinan, Bernice E. (Guilford Press International Literacy Association, 2018)
"This indispensable teacher resource and course text, now revised and updated, addresses the "whats," "whys," and "how-tos" of incorporating outstanding children's literature into the K-8 reading program. A strong emphasis on diverse literature is woven throughout the fifth edition, with chapters emphasizing the need for books that reflect their readers and presenting dozens of carefully reviewed books that teachers will be eager to use in the classroom. Leading authorities provide advice on selecting texts, building core literacy and literary skills, supporting struggling readers, and maximizing engagement. The volume offers proven strategies for teaching specific genres and formats, such as fiction, nonfiction, picturebooks, graphic novels, biographies, and poetry"-- Provided by publisher.